2019
DOI: 10.1155/2019/8592921
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Proliferation of Epstein–Barr Virus-Associated Human Nasopharyngeal Carcinoma Cells by Inhibiting EBV Nuclear Antigen 1 Expression

Abstract: This investigation aims to study the effect of curcumin on the proliferation, cycle arrest, and apoptosis of Epstein–Barr virus- (EBV-) positive nasopharyngeal carcinoma (NPC) cells. EBV+ NPC cells were subjected to curcumin treatment. The cell viability was evaluated with the CCK-8. Cell cycle and apoptosis were analyzed by flow cytometry analysis. Expression (protein and mRNA) levels were detected with western blotting and quantitative real-time PCR, respectively. Curcumin efficiently reduced the viability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The detailed method of Western blot assay was described in our previous publication [ 23 ]. Briefly, MCF7 and MDA-MB-468 cells were transfected with siRNA-SLC39A7 or the control siRNA for 48 h. Cells were rinsed, harvested and dissolved in RIPA lysis buffer (Beyotime Institute of Biotechnology, China) with 0.5% cocktail protease inhibitor (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed method of Western blot assay was described in our previous publication [ 23 ]. Briefly, MCF7 and MDA-MB-468 cells were transfected with siRNA-SLC39A7 or the control siRNA for 48 h. Cells were rinsed, harvested and dissolved in RIPA lysis buffer (Beyotime Institute of Biotechnology, China) with 0.5% cocktail protease inhibitor (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…The chemosensitizing effects of curcumin in EBV-positive cells may be explained by its capacity to modulate the EBV life cycle. Curcumin reduces levels of Epstein-Barr nuclear antigen 1, a critical protein for viral latency maintenance, promoting cell cycle arrest and apoptosis of EBV-nasopharyngeal carcinoma cells (46). Similarly, a previous study indicated that curcuminoids promote EBV lytic cycle reactivation, increasing the cell death of gastric and nasopharyngeal cell lines when combined with other lytic activators such as gemcitabine and valproic acid (15).…”
Section: Discussionmentioning
confidence: 92%
“…- Overexpression of Jab1 correlated with poor survival in NPC patients. Liu et al [ 43 ] HONE1 HK1 Curcumin MG-132 Effect of curcumin on the proliferation, cycle arrest, and apoptosis of EBV + NPC cells Curcumin induced EBNA1 degradation via the proteasome-ubiquitin pathway Friboulet et al [ 44 ] C666–1 CNE2 (EBV-) 13 NPC biopsies C15 and C17 (EBV + in nude mice) NPC xenografts MG132 Epoxomicin Functions of c-IAP2 in NPC cells - RMT 5265 induces the proteasome-mediated degradation of c-IAP2, resulting from the enhanced polyubiquitination of c-IAP2 Hui et al [ 45 ] HONE1, HK1-EBV, HONE1-EBV, HA, C666–1 Female BALB/c nude (nu/nu) mice Bortezomib, SAHA (Vorinostat) Mechanisms of apoptosis and effects on lytic cycle activation of EBV - Combination of bortezomib and SAHA synergistically induce killing of a panel of NPC cell lines and suppresses the growth of NPC xenografts in nude mice. - Bortezomib inhibits SAHA’s induction of EBV replication and abrogates production of infectious viral particles in NPC cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, treatment of NPC cells with proteasome inhibitors resulted in a significant increase of total p27 levels. In parallel, Jab1/CSN5 overexpression happened to be inhibited, which may therefore indicate that Jab1/CSN5 promotes p27 degradation through the ubiquitin-dependent proteasome pathway which in turn may lead to cell-cycle progression [ 43 ].…”
Section: Introductionmentioning
confidence: 99%